Developing an English Education Department Curriculum - Habiburrahim, Habiburrahim (SCAD Independent, 2017)
Curriculum is the heart of teaching and learning program. Through a curriculum, teachers formulate the designated learning objectives and their outcomes and transform all those formulated goals to students. This paper has an attempt to elaborate significant information and models on curriculum that could be developed at the English Education Department (PBI – Pendidikan Bahasa Inggris) of Ar-Raniry State Islamic University (UIN Ar-Raniry) Darussalam, Banda Aceh as an Islamic higher education institution. The paper reviews various literatures on language learning curriculum, teaching English as a foreign language curriculum, and professional learning curriculum. The paper also analyses the 2016/2017 UIN Ar-Raniry manual/handbook, and the 2015 annual report of the PBI department curriculum monitoring and evaluation (Monev). The findings elucidate that the PBI department curriculum has met a standardized curriculum quality. Yet, some weaknesses that could decelerate the language acquisition process are still found in such the PBI department curriculum.